HLA Loci and Recurrence of Focal Segmental Glomerulosclerosis in Pediatric Kidney Transplantation. Issue 10 (October 2021) - Shaw, Brian I.; Ochoa, Alejandro; Chan, Cliburn; Nobuhara, Chloe; Gbadegesin, Rasheed; Jackson, Annette M.; Chambers, Eileen T.
Abstract : Background: Recurrent focal segmental glomerulosclerosis (FSGS) after kidney transplantation accounts for the majority of allograft failures in children with primary FSGS. Although current research focuses on FSGS pathophysiology, a common etiology and mechanisms of disease recurrence remain elusive. Methods: We performed a retrospective review of the Scientific Registry of Transplant Recipients to determine the association of specific HLA recurrence of FSGS. Kidney transplants recipients under the age of 19 who were diagnosed with FSGS, who were transplanted after January 1, 2000, and who had complete HLA data were included in the study. We performed simple logistic regression on all HLA A, B, C, DR, and DQ represented in the dataset and FSGS recurrence and then determined those associated with recurrence using the Benjamini–Hochberg method for multiple comparisons. For those HLAs that were associated with recurrence, we further determined the effect of matching recipient and donor HLA with recurrence. Results: HLA DR7, DR53, DQ2, DR52, and DQ7 were associated with increased or decreased risk of recurrent disease after transplantation. We identified a risk haplotype consisting of HLA-DR7, DR53, and DQ2 that was consistently associated with an increased risk of recurrence (odds ratio 1.91; 95% confidence interval, 1.44-2.54, P < 0.001). We also found that donor/recipient concordance for HLA-DQ7 was associated with a decreased risk of recurrence (odds ratio 0.42; 95% confidence interval, 0.37-0.53, P = 0.009). Conclusions: HLA profiles may be used for risk stratification of recurrence of FSGS in pediatric kidney transplant recipients and deserves further study.